2019
DOI: 10.1038/s41598-018-37268-1
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of fetal intraabdominal extralobar pulmonary sequestration: a 12-year 3-center experience in China

Abstract: To provide useful information for diagnosing and predicting fetal intraabdominal extralobar pulmonary sequestration (IEPS), a retrospective review of diagnostic approaches was conducted. Ultrasonography was performed serially in 21 fetuses with IEPS from 2005 to 2017. Prenatal sonographic features, treatment, and outcomes of each case were evaluated and collected. These cases of IEPS were also compared to 43 cases previously reported by other researchers from 1986 to 2017. Of the 21 sonographic features, 14 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…We report several prenatal ultrasound and MRI findings that were significantly associated with the diagnosis of a pulmonary sequestration in comparison to adrenal hemorrhage, which were the most common assigned diagnoses in our suprarenal lesions. In contrast to adrenal hemorrhages, pulmonary sequestrations were uniformly left-sided in this series, which is consistent with prior studies reporting a high frequency of left-sidedness [5,15]. Moreover, pulmonary sequestrations were more likely to be diagnosed earlier in gestation and have specific imaging features including a feeding vessel, solid composition with an echogenic appearance on ultrasound, and low T1 MRI signal.…”
Section: Discussion/conclusionsupporting
confidence: 89%
“…We report several prenatal ultrasound and MRI findings that were significantly associated with the diagnosis of a pulmonary sequestration in comparison to adrenal hemorrhage, which were the most common assigned diagnoses in our suprarenal lesions. In contrast to adrenal hemorrhages, pulmonary sequestrations were uniformly left-sided in this series, which is consistent with prior studies reporting a high frequency of left-sidedness [5,15]. Moreover, pulmonary sequestrations were more likely to be diagnosed earlier in gestation and have specific imaging features including a feeding vessel, solid composition with an echogenic appearance on ultrasound, and low T1 MRI signal.…”
Section: Discussion/conclusionsupporting
confidence: 89%
“…Additionally, according to our study, drainage veins may be associated with this anomaly. To date, the feeding artery is assessed to diagnose EPS; thus, there are few reports on assessing drainage veins for diagnosis 9,10,20,21 . Moreover, ultrasound was unable to visualize the drainage vein; however, CT was useful for the evaluation of vascular anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…As most PS cases remain asymptomatic after birth, intrusive pathological diagnosis can hardly be obtained in a large surveillance system like CBDMN. Some comparative studies have revealed a high concordance (> 90%) between prenatal ultrasound diagnosis and postoperative pathological confirmation [ 4 , 45 ]. For the past 30 years, sonographic technology has been widely used in China for the prenatal and postnatal detection of structural malformations, including PS [ 23 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely accepted theory is that PS results from the formation of an accessory lung bud below the normal lung buds [2]. It may occur as an isolated lesion or in association with other malformations [2][3][4]. Clinically, PS cases are usually divided into the intralobar and extralobar types.…”
Section: Introductionmentioning
confidence: 99%